The problems raised by the testament in private international relations: A comparative study - Bencheikh el Fegoun, Soumia; BENCHABENE, Mohamed Salah (Journal of Human Sciences, 2020)
The testament that includes a foreign element raises many problems in light of private international relations, most notably the problem of conflicts of adaptations, the legislation differed about their adaptation, while the Algerian legislator included them in the category of personal status and subjected to personal law, in addition to the problem of conflict of laws, and difficulty Finding the appropriate base for resolving the issue in dispute. In the same context, the Algerian legislator submitted the substantive conditions of the testament to the law on the nationality of the testator at the time of his death, while his formal requirements as an act of the law of the testator at the time of thetestament or of the law of the country in which it was made.